Activation and Functional Alteration of Mucosal-Associated Invariant T Cells in Adult Patients With Community-Acquired Pneumonia - Ouyang, Lichen; Wu, Mi; Shen, Zhijun; Cheng, Xue; Wang, Wei; Jiang, Lang; Zhao, Juan; Gong, Yeli; Liang, Zhihui; Weng, Xiufang; Yu, Muqing; Wu, Xiongwen (Frontiers in Immunology, 2021)
Community-acquired pneumonia (CAP) remains the significant infectious cause of morbidity and mortality worldwide. Although mucosal-associated invariant T cells (MAIT) play roles in the pathogenesis of children CAP and ICU-associated pneumonia, their roles in adult CAP are largely unexplored. In this study, we investigated the frequency, phenotype, and function of MAIT cells in peripheral blood and bronchoalveolar lavage fluid (BALF) of adult CAP patients. Our data indicate that MAIT-cell frequency is profoundly lower in the peripheral blood of CAP patients compared to that in healthy individuals. Furthermore, the circulatory MAIT cells express higher levels of CD69 and PD-1 compared to those in healthy individuals. In BALF of CAP patients, MAIT-cell frequency is higher and MAIT cells express higher levels of CD69 and PD-1 compared to their matched blood counterparts. Levels of IL-17A and IFN-γ are increased in BALF of CAP patients compared to those in BALF of patients with pulmonary small nodules. The IL-17A/IFN-γ ratio is significantly positively correlated with MAIT frequency in BALF of CAP patients, suggesting a pathogenic role of MAIT-17 cells in CAP. Of note, blood MAIT-cell frequency in CAP patients is strongly negatively correlated with high-sensitivity C-reactive protein (hsCRP) and neutrophil count percentage in blood. The ability of circulating MAIT cells in CAP patients to produce IFN-γ is significantly impaired compared to those in healthy individuals. In summary, our findings suggest the possible involvement of MAIT cells in the immunopathogenesis of adult CAP.